2016
DOI: 10.9713/kcer.2016.54.4.568
|View full text |Cite
|
Sign up to set email alerts
|

Contact Charging and Electrphoresis of a Glassy Carbon Microsphere

Abstract: − We investigated the charging characteristics of a conducting solid sphere (glassy carbon sphere) comparing with that of a water droplet and check the applicability of the perfect conductor theory. For the systematic research, sphere size, applied voltages, viscosity of the medium were changed and the results were compared with that of corresponding water droplets and the perfect conductor theory. Basically, a glassy carbon sphere follows the perfect conductor theory but the charging amount was lower as much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…With more accurate drag calculations, such as a full three-dimensional numerical analysis, one can expect that all dimensionless charges will be unity or slightly higher due to the deformation effect. The present findings also explain the charging behavior of a glassy carbon sphere, which showed 20–30% less dimensionless charges than theoretical predictions and also showed the decreasing trends of dimensionless charges for larger solid spheres …”
Section: Resultssupporting
confidence: 74%
“…With more accurate drag calculations, such as a full three-dimensional numerical analysis, one can expect that all dimensionless charges will be unity or slightly higher due to the deformation effect. The present findings also explain the charging behavior of a glassy carbon sphere, which showed 20–30% less dimensionless charges than theoretical predictions and also showed the decreasing trends of dimensionless charges for larger solid spheres …”
Section: Resultssupporting
confidence: 74%
“…The CCEP of a water droplet has been successfully explained by classical electrostatics of a perfect conductor. 3,18,20,32,40,42 This perfect conductor theory predicts that when a conductive sphere is brought in contact with an electrified electrode, the sphere is charged as a result of redistribution of electric field around the sphere, and the corresponding charge amount Q theory is given as 20…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Especially, nobody could clearly explain the origin of the charging amount difference between positive and negative electrodes, although there were lots of works reporting this difference 3,32,39−41 even in experiments using a solid sphere. 13,42 In previous work, this positive and negative charging difference was believed to be linked to the electrochemical reaction rate difference in each separate charging (positive and negative) because the charge transfer through pure water should involve electrolysis of water and the electrochemical reaction of each charging is different (oxygen formation on positive charging and hydrogen formation on negative charging). 3,40 However, the positive and negative charging difference observed in solid sphere experiments 13,42 implies that the difference can be originated from physical origins rather than from electrochemical origins.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaling analysis revealed that droplet CCEP can be explained according to a perfect conductor theory. , Later, the contact charge was analyzed by normalizing it to the theoretical maximum charge derived by the perfect conductor theory called Maxwell charge. ,,, For accurate charge measurement, a rigorous study has been conducted on the drag of a moving droplet and high-resolution electrometer was used to directly measure the droplet charge. , In many reports, the charge acquired by aqueous droplets was less than the Maxwell charge . Even in experiments with solid conductor spheres, less charging behavior was observed. , To account for this insufficient charging, imperfections on the electrode surface because of the formation of craters on the electrode surface have been proposed . These rigorous studies have greatly improved our understanding of CCEP.…”
Section: Introductionmentioning
confidence: 99%